1981
DOI: 10.1042/cs0610339
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Interaction of Elastic and Flow-Resistive Respiratory Loads in Man

Abstract: 1. The detection of added inspiratory airflow resistances was studied in normal individuals under two circumstances: first, while breathing unhindered, and secondly, while breathing against continuously applied ('basal') inspiratory elastic loads. The addition of basal elastic loads resulted in impaired detection of flow-resistive loads whether expressed as added flow resistance or as a proportion of the basal flow resistance. 2. When loads were plotted on a logarithmic scale, load-detection relationships were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In an unpublished study, we found load detection was slightly reduced (0.6 cmH20 I-IS-I � 1.0 cmH20 I-IS-I) when loads were added around the chest rather than at the mouth. This reduction can be accounted for by the increase in background elastance due to phase differences in pressure around the chest (45). When loads are added around the chest cage, many subjects localize the detection of load to the mouth.…”
Section: Basic Sensationsmentioning
confidence: 98%
“…In an unpublished study, we found load detection was slightly reduced (0.6 cmH20 I-IS-I � 1.0 cmH20 I-IS-I) when loads were added around the chest rather than at the mouth. This reduction can be accounted for by the increase in background elastance due to phase differences in pressure around the chest (45). When loads are added around the chest cage, many subjects localize the detection of load to the mouth.…”
Section: Basic Sensationsmentioning
confidence: 98%